Solving Coupled Hirota System by Using Homotopy Perturbation and Homotopy Analysis Methods - Saeed, Rostam K.; Muhammad, Rebwar S. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, two methods, namely Homotopy Perturbation Method (HPM) and Homotopy Analysis Method (HAM) are applied to obtain approximate solutions of the nonlinear coupled Hirota system (CHS). We see that these two methods are efficient and effectives for solving nonlinear CHS and the obtained results of the two methods coincide with each other. In our work, Maple 13 has been used for computations.
Keywords: Homotopy Perturbation Method; Homotopy Analysis Method; Coupled Hirota System; analytical solution